Bioactive Compounds of the Ethanol Extract of Butterfly Pea Petals (Clitorea ternatea L.) on Gastric Proton Pump: In-Silico Analysis - Kurniawati, Atik; Lestari, Sri Rahayu; Rohman, Fatchur (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
The biodiversity of medicinal plants in Indonesia reflects the potential to be used to treat non-communicable diseases such as cancer. Gastritis is a kind of symptom felt in the stomach that may trigger severe abnormalities leading to a state of cancer. This study aims to determine the potential of bioactive compounds derived from the ethanol extract of butterfly pea petals (Clitoria ternatea L.) as an in-silico anti-gastritis drug candidate. This study was a descriptive study with a qualitative approach. The molecular docking method applied specific docking using PLANTS software. The results of molecular docking indicated that there might be a similar potential as the control drug in inhibiting the gastric proton pump. Based on the analysis of the LCHRMS results, flavonoid compounds in the extract of butterfly pea petals were found to be used for docking analysis. Each flavonoid compound and the docking score from highest to lowest were Rutin (-87.05), Quercetin-3β-D-glucoside (-79.30), Quercetin (-79.28), Kaempferol (-74.80), Trifolin (-74.22), Genistein (-69.70), Kaempferol-3-glucoside-3''rhamnoside (-67.79), Biochanin A(1−) (-67.64), and Mauritianin (-58.26). The flavonoid compound named Rutin had the highest docking score above the two control drugs of Omeprazole (-66.27) and Vonoprazan (-84.45). It can be concluded that based on the in-silico study, the flavonoid compound of Rutin in the ethanol extract of butterfly pea petals (Clitoria ternatea L.) had the potential to inhibit the gastric proton pump to prevent gastritis. The chemical structure of Rutin differs from the two control drugs because it has a more complex structure consisting of five benzene rings. Further dynamic molecular tests are recommended to find out which flavonoid compounds have the most stable affinity for the target protein. Based on the in-silico test, in vivo and in vitro studies should be performed to find out more information about the potential of the flavonoid compounds in butterfly pea extract to inhibit the action of the gastric proton pump.